Structure features and paramagnetic centres in oxide nanopowders - Shevchuk, V.N.; Popovych, D.I.; Usatenko, Yu.N.; Demchenko, P.Yu.; Serkiz, R.Ya. (Functional Materials, 2009)
Nanopowders ZnO, SiO₂, SiO₂/10 % V₂O₅ obtained by sol-gel technology were investigated by electron paramagnetic resonance (EPR) method at temperature of liquid nitrogen. The structures of the samples are analyzed by X-ray diffraction method. Surface morphology and chemical elementwise composition of powders were studied using scanning electron microscopy. For the nanocomposite SiO₂/10 % V₂O₅ structure of EPR spectrum is described as a result of unpaired electron and isotope nucleus ⁵¹V interaction. The prevailed EPR signal in ZnO is hypothetically associated with single-charge vacancy in oxygen sub-lattice. Нанопороmки ZnO, SiO₂, SiO₂/10 % V₂O₅, отримані за sol-gel- технологією досліджено методом електронного парамагнітного резонансу (ЕПР) при температурі рідкого азоту. Структуру зразків проаналізовано з використанням методу рентгенівської дифракції. Морфологію поверхні та хімічний елементний склад порошків вивчено скануючим електронним мікроскопом. Для нанокомпозиту SiO₂/10 % V₂O₅ структура ЕПР спектра приписується результату взаємодії неспареного електрона з ядром ізотопу ⁵¹V. Домінуючий сигнал ЕПР у ZnO попередньо пов'язується з однозарядною вакансією у кисневій підгратці. Нанопорошки ZnO, SiO₂, SiO₂/10% V₂O₅, полученные по sоl-gеl-технологии, исследованы методом электронного парамагнитного резонанса (ЭПР) при температуре жидкого азота. Структура образцов проанализирована с использованием методарентгеновской дифракции. Морфология поверхности и химический элементный состав порошков изучался сканирующим электронным микроскопом. Для нанокомпозита SiO₂/10 % V₂O₅ структура ЭПР спектра приписывается результату взаимодействия неспаренного электрона с ядром изотопа ⁵¹V. Доминирующий сигнал ЭПР в ZnO предварительно связывается с однозарядной вакансией в кислородной подрешетке.